Analysis of functioning and role of Foster Groups in community mental health care. Lima, Peru, 2019. - Castillo-Martell, Humberto (2022)
Objective: The operationalization and the role of a participatory model of diagnostic and therapeutic formulations called Foster Groups, implemented in a Community Mental Health Center in Lima, Peru, are analyzed. Material and Methods: The research was based on the participanting observation by experts in community mental health, public health, communication and social sciences, of a total of 24 Foster Group sessions held at the Nancy Reyes Community Mental Health Center in Chorrillos, Lima Peru, during the years 2018-2019. Results: The Foster Groups are structured in sequential phases that follow a logical process of diagnostic formulations and management plans, concurrently performed by professionals from different disciplines for a small group of users, thus allowing both, diagnoses as plans, to be more comprehensive. An environment of trust is generated, allowing people to share experiences of suffering and intimacy at levels that often exceed those expressed in the traditional doctor-patient relationship. Interdisciplinary dialogue is permanent and users alternate roles of analysands and analysers, showing signs of progressive empowerment. Conclusions: Foster Groups operationalize the fundamental principles of Community Mental Health, are a valuable tool for the expansion of the Comprehensive Care Model as the axis of public health policy in Peru, soften the communication barriers of the doctor-patient relationship, and reduce the social distances between participants, enabling better care and therapeutic alliances.